Rancang Bangun Meja Laboratorium Komputer Jurusan Teknik Industri Universitas PGRI Ronggolawe Tuban dengan Pendekatan Ergonomi - Saputra, Dwi; Sanjaya, Krishna Tri; Nuruddin, Abdul Wahid; Wibowo, Moh. Muhyidin Agus (IMEJ (Jurnal Teknik dan Managemen Industri), 2022)
The computer laboratory is one of the facilities for industrial engineering study program students at the Pgri Ronggolawe University, Tuban. The table is one of the most closely related factors in improving the quality of learning. In many cases, poor posture when sitting is the main cause of back, waist, shoulder or neck pain. If every day a person moves in front of a computer screen, it should be noted that the computer screen should be adjusted to the eye. The purpose of this research is to improve the ergonomic desk design. Ergonomics also deals with optimization, efficiency, health, safety and human comfort at work, at home and in recreation areas. In ergonomics, it is necessary to study the system in which humans, work facilities and the environment interact with each other with the main goal of adjusting the work atmosphere to the humans. Thus, it is necessary to have an innovation to produce a computer desk that pays attention to ergonomic values. The hypothesis of this study is that having a computer laboratory table made on the basis of ergonomics will increase the effectiveness, comfort, safety, health and efficiency of the table.